NILAI KARAKTER DALAM CERITA RAKYAT ASAL MULA RAWA UMBUNG DAN RELEVANSINYA UNTUK PEMBELAJARAN BAHASA INDONESIA - Neti Erlina; Mastiah Mastiah (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
ABSTRACT This study is based on the importance of strengthening character education through contextual learning based on local culture. This study aims to examine the character values ​​contained in the folktale "Asal Mula Rawa Umbung" and explain their relevance to Indonesian language learning in elementary schools. The study employed a descriptive qualitative method, using the text of the folktale "Asal Mula Rawa Umbung" as its data source, contained in a collection of Melawi folktales. Data were collected through reading, note-taking, literature review, interviews, observation, and documentation. Data validity was tested through technical triangulation and increased researcher diligence. The results indicate that the folktale "Asal Mula Rawa Umbung" contains several character values, including hard work, creativity, friendship or communication, social awareness, and responsibility. These values ​​are reflected in the actions of the characters and the series of events that form the storyline. Furthermore, this folktale is relevant for use in Indonesian language learning in elementary schools because it can be used as teaching material that not only improves students' language skills but also instills character values ​​and introduces them to local culture. Thus, the use of folk tales in the learning process can support the strengthening of character education while preserving local wisdom. ABSTRAK Penelitian ini didasarkan pada pentingnya penguatan pendidikan karakter melalui pembelajaran kontekstual berbasis budaya lokal. Penelitian ini bertujuan untuk mengkaji nilai-nilai karakter yang terkandung dalam cerita rakyat Asal Mula Rawa Umbung serta menjelaskan keterkaitannya dengan pembelajaran Bahasa Indonesia di sekolah dasar. Penelitian menggunakan metode deskriptif kualitatif dengan sumber data berupa teks cerita rakyat Asal Mula Rawa Umbung yang terdapat dalam buku kumpulan cerita rakyat Melawi. Data dikumpulkan melalui teknik membaca, mencatat, studi pustaka, wawancara, observasi, dan dokumentasi. Keabsahan data diuji melalui triangulasi teknik serta peningkatan ketekunan peneliti. Hasil penelitian menunjukkan bahwa cerita rakyat Asal Mula Rawa Umbung memuat beberapa nilai karakter, antara lain kerja keras, kreatif, bersahabat atau komunikatif, peduli sosial, dan tanggung jawab. Nilai-nilai tersebut tercermin dari tindakan para tokoh serta rangkaian peristiwa yang membentuk alur cerita. Selain itu, cerita rakyat ini relevan digunakan dalam pembelajaran Bahasa Indonesia di sekolah dasar karena dapat dimanfaatkan sebagai bahan ajar yang tidak hanya meningkatkan keterampilan berbahasa siswa, tetapi juga menanamkan nilai-nilai karakter serta memperkenalkan budaya lokal kepada peserta didik. Dengan demikian, pemanfaatan cerita rakyat dalam proses pembelajaran dapat mendukung penguatan pendidikan karakter sekaligus menjaga kelestarian kearifan lokal.